Assessing the Spiritual Health in Nurses of Critical Care Units: A Cross-Sectional Study - Shohreh Javadpour (Journal of Global Pharma Technology, 2017)
Introduction: Intensive care unit due to critical ill patients and its special situation, require nurses who can take care for patients in their best manner. Spiritual health as one of the important aspects of the health, along with other aspects such as physical, mental and social aspects, has an important role in providing useful and effective care by nurses in critical care units. This study was aimed to assess spiritual well-being in the intensive care unit nurses. Methods: In this cross-sectional study, 53 nurses of critical care units were studied. Census method is done for sampling and study was conducted according to informed consent of intensive care unit nurses of Jahrom University of Medical Sciences in 1394. The data collection tool was a valid and reliable questionnaire of spiritual health (r=0.8), consisted of 28 questions related to attitude and 20 questions related to the performance. The questionnaire had 5-point Likert scale: absolutely agree (score= 100), almost agree (score= 75), neutral (score=50), almost disagree (score= 25) and strongly disagree (score= 0). Collected information was analyzed by SPSS software for the descriptive statistics. Results: Of total of 53 nurses, 94.3% (n = 50) were female, 66% (n = 35) were married and 98.1% (52 patients) had nursing bachelor´s degree. The average age of nurses was 32.06 ± 6.23. 49.1% (26 patients) worked in the ICU and others worked at CCU and dialysis wards. Median attitude towards spiritual health was90.18 (82.14 - 97.32) and median healthy spiritual performance was82.50 (75.00- 88.75).The total median of spiritual health in the population of critical care nurses was85.42 (79.17- 91.67)Conclusion: The spiritual health score is generally good in the intensive care unit nurses, although due to the difference between spiritual insight and action, special attention should be done to enhance better healthy practice and consequently intensive care unit nurses who are exposed to high stress situation, can benefit the spiritual health and as a result, patients receive better nursing care.Keywords: Spiritual health, Nurse, Attitude, Critical care